2021
DOI: 10.9745/ghsp-d-21-00144
|View full text |Cite
|
Sign up to set email alerts
|

New Mixed Methods Approach for Monitoring Community Perceptions of Ebola and Response Efforts in the Democratic Republic of the Congo

Abstract: Ebola-affected communities in the eastern Democratic Republic of the Congo had questions about the outbreak, doubts about the reality of Ebola, and concerns about health care and the Ebola vaccination program.n In peak outbreak areas, beliefs that Ebola response teams were stealing organs and bodies declined after burial teams introduced transparent body bags. Similarly, calls for making vaccination "more fair" declined after Ebola vaccination eligibility was expanded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…This work of data collection, coding and thematic analysis allowed for the creation of weekly briefs by geographical zone, deep-dive briefs, trend analyses and specialised presentations for field-level and strategic decision-making. A dashboard of the CF (coded) was also made available to all response partners 16…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This work of data collection, coding and thematic analysis allowed for the creation of weekly briefs by geographical zone, deep-dive briefs, trend analyses and specialised presentations for field-level and strategic decision-making. A dashboard of the CF (coded) was also made available to all response partners 16…”
Section: Methodsmentioning
confidence: 99%
“…12 13 Additional detail about the system itself is described elsewhere. [14][15][16] The structure of the DRC Ebola response changed over time, but remained organised around technical 'commissions' or pillars (see figure 1), based on the WHO's Incident Management System. 17 These pillars were largely the same at all levels of the DRC Ebola response.…”
Section: Key Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…These may be the consequence of the low level of education among the population and their lack understanding of the disease (23). Indeed, Mueller et al reported an increase in violence against HCWs during the Ebola outbreak in North Kivu (20) that can be explained by the perception of Ebola as a conspiracy not only to raise money but also to exterminate a part of the population (51). Cai et al in China reported that the perpetrators' perception of professional misconduct after the death of a loved one was the main cause of the various forms of aggression towards HCWs (52).…”
Section: Types and Causes Of Violence Against Health Workersmentioning
confidence: 99%